Heterogeneous multidimensional efficiency effects of agro-ecological pest management transition and intensification in smallholder systems–evidence from mango fruit fly control in Kenya - Owili, S.O.; Otieno, D.J.; Chimoita, E.L.; Baijukya, F.P. (2025)
Agro-ecological transition is an important step towards sustainable and resilient food systems in the face of systemic threats from climate-change-induced disturbances. In smallholder systems, the transition towards agro-ecological pest management (APM) offers the prospect of reconciling agronomic performance with environmental and social imperatives by replacing indiscriminate chemical applications with locally-derived biorational options. However, the efficiency implications of APM transitions remain insufficiently documented, particularly in smallholder systems and in relation to invasive alien pests that are prone to resurgence and reinfestation under suboptimal management. This paper evaluates whether the adoption and intensification of APM improve both technical and eco-efficiency in smallholder settings, with a focus on the Oriental fruit fly (Bactrocera dorsalis L.) in mango (Mangifera indica L.) orchards. We apply a latent class stochastic metafrontier model to a sample of 418 orchard managers from Makueni County, Kenya, selected through a multistage sampling procedure. This approach enables us to classify orchard managers into non-adopters, nonintensive adopters, and intensive adopters, and to compute meta-technical and meta-eco-efficiency scores, from which we derive an environmentally adjusted efficiency measure. We find no significant sample selection bias and treatment effects are estimated using a doubly robust Inverse-probability-weighted regression adjustment estimator. Intensive adoption had a positive average treatment effect (ATE) and average treatment effect on the treated (ATT) of 8.1% and 5.6%, respectively, whereas non-intensive adoption showed no significant effect (ATE = –1.1%, ATT = –1.5%). Efficiency effects were heterogeneous and inefficiency varied with orchard manager’s APM adoption intensity, education level, orchard prospects, group membership, and participation in knowledge co-creation activities. Policymakers and development practitioners should support farmers by institutionalising continuous learning and establishing multi-pronged participatory training platforms that use existing social networks.